A Process for Convenient Production of Hygienic Fish Sauce by Lactic acid Fermentation of Shark Meat Gel - R.S., Sree Rekha; M.D., Alur; V., Venugopal (Fishery Technology, 2025)
A process is described to prepare hygienic sauce from shark meat by lactic acid fermentation. Whole shark (Scoliodon laticaudus) was eviscerated, beheaded and deboned. The meat pieces were soaked overnight in cold water, drained, homogenized in water and converted into a gel by lowering the pH to 3.5 by acetic acid. The gel was fermented by Lactobacillus casei for 3 days at 30Â°C. Fermentation was monitored by measuring growth of the organism, pH fall and utilization of carbohydrates. The product was characterized by sour taste and negligible fishy odour. Since the shark meat gel has a refrigerated shelf life of 2 months, the process helps in convenient preparation of sauce.